Gender Analysis of “Lakon Di Kota Kecil”: The Short Story Collection by Ratna Indraswari Ibrahim as a Feminist Literature Study of the Indonesian Moslem Writer’s Literary Work: English - Risma Amin (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Gender analysis in the short story collection Lakon di Kota Kecil by Ratna Indraswari Ibrahim aimed to reveal gender relations and patriarchal culture, illustrated by this Moslem writer. This research uses a based gender literary approach by using feminist literary criticism. This also used the short story structural theory, specifically about characterizations. In this short story collection, i found eleven short stories from twenty short stories depicting a woman who obeys patriarchal culture, while nine other short stories reflect the antithetical narration. The gender ideology adopted by the characters can confirm the patriarchal culture and lead to gender injustice. So the characters who oppose patriarchal culture can achieve gender justice. Several characters had been free from the strain to guide their lives according to their desires in this short story collection from a feminist perspective. Also, it implies the women’s struggle in getting equal awareness like men. While the forms of gender injustice in women figures are marginalization, subordination, and stereotype